Politica şi practica privind integrarea imigranţilor şi refugiaţilor în statele europene - Radu, Mircea (Calitatea Vieții, 2006)
The article tackles a nowadays issue in European states regarding the phenomenon of integration of immigrants in these communities from two perspectives: the governmental policies and the practices of implementation of policies. In the first part, it is presented a short analisys on the integration concept of refugees and immigrants, the former being a special category of immigrants who need special measures for their integration. The researches presented here noticed that there is a general tendency to operate a difference between refugees and other categories of immigrants, especially economical immigrants, because the former need a longer period of assistance and in certain cases special measures firstly justified by their reasons to leave their countries of origin (a forced exile), although at the policy level it is not seen a clear difference between these two categories of migrants. In the second part, we can read about the theoretical models of policies which aim at the integration of immigrants and refugees, the main elements of these policies, the practices in European countries and also the vision of European Commission on this issue. It is worth to be mentioned that at the level of European Union was endorsed a set of basic principles in order to promote a common European vision on the immigrant integration, the principles which will represent a base for the future policies in integration area. At the end, it is presented an overview on Romanian situation which emphasizes that in our country the European standards are accomplished. At the moment, there is a coherent policy and legislation, the institutional framework to put in practice the legislation and actual integration programs.